2009
DOI: 10.1074/jbc.m806774200
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-dependent Phosphorylation of PTEN Mediates Actin Restructuring and Activation of ATP-sensitive K+ Channels

Abstract: Leptin activates multiple signaling pathways in cells, including the phosphatidylinositol 3-kinase pathway, indicating a degree of cross-talk with insulin signaling. The exact mechanisms by which leptin alters this signaling pathway and how it relates to functional outputs are unclear at present. A previous study has established that leptin inhibits the activity of the phosphatase PTEN (phosphatase and tensin homolog deleted on chromosome 10), an important tumor suppressor and modifier of phosphoinositide sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 51 publications
(92 reference statements)
3
35
0
Order By: Relevance
“…Thus, PTEN and GSK3␤ seem to serve as downstream signals for leptin-caused F-actin rearrangement. In agreement with our results, leptin treatment also causes F-actin depolymerization via PTEN and GSK3␤ in hypothalamic neuronal cells (16,22). PTEN directly regulates actin-depolymerizing factor cofilin-1 in alveolar macrophages (42).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, PTEN and GSK3␤ seem to serve as downstream signals for leptin-caused F-actin rearrangement. In agreement with our results, leptin treatment also causes F-actin depolymerization via PTEN and GSK3␤ in hypothalamic neuronal cells (16,22). PTEN directly regulates actin-depolymerizing factor cofilin-1 in alveolar macrophages (42).…”
Section: Discussionsupporting
confidence: 80%
“…In our previous study, leptin treatment augmented the expression of phosphorylated PTEN and GSK3␤ in hypothalamic neuronal cells (16), which led to repressed PTEN-GSK3␤ signaling. Moreover, the study showed that leptin treatment increased ciliary length by inhibiting the PTEN-GSK3␤ pathway.…”
Section: Leptin Treatment Elongates Hypothalamic Neuronal Ciliamentioning
confidence: 99%
“…A number of signaling molecules, including PI3K and tyrosine kinases, were implicated in early studies (14,16), although their roles were not further substantiated. Subsequent studies show that leptin causes inhibition of the lipid/protein phosphatase PTEN, accumulation of PIP 3 , and F-actin depolymerization, events that correlate with increased K ATP conductance (15,18,19). Despite these efforts, the molecular and cellular events following leptin stimulation that lead to increased K ATP activity remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, leptin-driven inhibition of PTEN would also result in elevated PtdIns(3,4,5,)P 3 levels. In support of a possible role for PTEN, leptin activation of hypothalamic K ATP channels reportedly involves inhibition of PTEN [38]. Similarly in hippocampal neurons, expression of dominant-negative PTEN mutants (C124S or G129E) not only mirrored but also occluded the leptin-driven increase in GluA1 surface expression, suggesting involvement of PTEN inhibition in this process.…”
Section: A Key Role For Phosphatase and Tensin Homologue In The Regulmentioning
confidence: 99%